1955
DOI: 10.1111/j.1749-6632.1955.tb45973.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pretreatments and Posttreatments on Bacterial Inactivation by Ionizing Radiations

Abstract: An evaluation of the available information concerned with the mode of lethal action of ionizing radiations on bacterial cells leads to the conclusion that alteration of relatively few molecules within the cell must ultimately bring about its inactivation. I t is possible that a chain reaction is initiated by the radiation that results in the destruction of a large number of biologically important molecules. The previous paper has discussed the improbability that a radiochemical chain reaction is of importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1956
1956
1978
1978

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It is a common experience among workers in this field that radiation survivors may need 2-3 weeks incubation in broth before growth occurs, and the work of Stapleton (1955) and others has shown that certain bacteria may recover from the effects of irradiation if they are incubated a t suboptimal temperatures or in the presence of certain metabolites. It would therefore seem desirable that further work should be done on this topic.…”
Section: Dose (Mnd)mentioning
confidence: 99%
“…It is a common experience among workers in this field that radiation survivors may need 2-3 weeks incubation in broth before growth occurs, and the work of Stapleton (1955) and others has shown that certain bacteria may recover from the effects of irradiation if they are incubated a t suboptimal temperatures or in the presence of certain metabolites. It would therefore seem desirable that further work should be done on this topic.…”
Section: Dose (Mnd)mentioning
confidence: 99%
“…Roepke & Mercer (1947) counted X-irradiated E. coli on three different media and found that all gave similar counts a t low mortalities, but significantly different counts a t high mortalities; Alper & Gillies (1958) have reported similar results. Stapleton (1955) incubated E. coli a t different temperatures following X-ray exposure and found that 18" was optimal for recovery. Inspection of these data shows that the greater the dose, and therefore the mortality, the greater the relative beneficial effect of incubation a t 18".…”
mentioning
confidence: 99%
“…That the action of M .r . extract under these conditions may be more closely related to procedures such as liquid-holding recovery (Stapleton 1955) was shown by the observation that, on incubation in M .r . extract for 5 or 15 min after irradiation in buffer, E. coli B/r showed increased survival, comparable to a dose modification factor (d .m .f.)…”
Section: Resultsmentioning
confidence: 93%